THE INFLUENCE OF THE ROLE OF INTERNAL AUDITORS, INTERNAL CONTROL, GOOD GOVERNMENT GOVERNANCE, FRAUD PREVENTION ON THE PERFORMANCE OF PROVINCIAL GOVERNMENTS NORTH SUMATERA WITH AS ETHICS INTERVENING VARIABLES - Wardhani, Neng Sri (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
The purpose of this study is to find out how much influence the role of Internal Auditor, Internal Control, Good Government Governance, Fraud Prevention Against Local Government Performance of North Sumatra Province With Ethnics as Intervening Variables directly or indirectly and whole simultaneously and partially. This research was conducted at Government office of Inspectorate of North Sumatra Province. This study uses path analysis techniques to test hypotheses and quantitative approaches, descriptive and associative types. The data used are primary data collected through questionnaires with a total sample of 31 respondents from internal auditors at the Inspectorate Office of North Sumatra Province. The results showed that (1) The role of Internal Auditor, Internal Control, Fraud Prevention has no direct significant effect on Ethics. Only Good Governance variable has a direct significant effect on Ethics. (2) The role of Internal Auditor, Internal Control, Good Government Governance, Fraud Prevention has no significant effect on Local Government Performance of North Sumatra Province. (3) Ethics has no significant effect on Local Government Performance of North Sumatra Province.